Causes and Consequences of Multi-Locus Imprinting Disturbances in Humans. Issue 7 (July 2016) - Sanchez-Delgado, Marta; Riccio, Andrea; Eggermann, Thomas; Maher, Eamonn R.; Lapunzina, Pablo; Mackay, Deborah; Monk, David
Abstract : Eight syndromes are associated with the loss of methylation at specific imprinted loci. There has been increasing evidence that these methylation defects in patients are not isolated events occurring at a given disease-associated locus but that some of these patients may have multi-locus imprinting disturbances (MLID) affecting additional imprinted regions. With the recent advances in technology, methylation profiling has revealed that imprinted loci represent only a small fraction of the methylation differences observed between the gametes. To figure out how imprinting anomalies occur at multiple imprinted domains, we have to understand the interplay between DNA methylation and histone modifications in the process of selective imprint protection during pre-implantation reprogramming, which, if disrupted, leads to these complex imprinting disorders (IDs). Trends: Imprinted DMRs represent a small minority of the methylation differences between gametes, but somatic protection of these elements is essential to avoid developing imprinting disorders (IDs). A subset of patients with IDs have methylation defects at single disease-associated imprinted differentially methylated regions, but other individuals may have MLID affecting additional imprinted regions. The frequency and loci involved in MLID varies between IDs, with patients with Beckwith–Wiedemann syndrome presenting with the highest and most severe MLID cases, while this phenomenon has not been reported in patients with Angelman or Temple syndrome. To date, mutations in three trans -acting factors (ZFP57, NLRP2, and NLRP5) have been associated with MLID.